(untitled) (Journal of Surgical Sciences, 2022)
Hydatid disease (cystic echinococcosis) is a helminthic infection caused by the larval stages of Echinococcus granulosus. This disease mainly affects the liver followed by lungs, kidney, bones, and brain. Simultaneous involvement of two organs occurs in about 5–13% of the cases. Gastrointestinal echinococcosis may result from a direct digestive localization of hydatid cyst but most often results from the rupture or fistulization in the digestive tract from other sites like liver. Involvement of the stomach remains an exceptional entity. A 35 year old male presented to the Surgery Department of Shaheed Suhrawardy Medical College and Hospital with the complaints of mild epigastric pain and occasional vomiting for one year. Per abdominal examination showed a non tender epigastric lump. CT scan of abdomen demonstrated a multiloculated cystic lesion in the right lobe of liver and another in the lesser sac in front of pancreas. Exploratory laparotomy was done which revealed a multiloculated cystic lesion in the right lobe of liver and another cyst attached to the posterior wall of stomach. Deroofing followed by irrigation with scolicidal agent and omentoplasty was done for both the cysts. His postoperative recovery was uneventful. Journal of Surgical Sciences (2022) Vol. 26(1) : 53-57